Hydroxychloroquine Does Not Increase the Risk of Cardiac Arrhythmia in Common Rheumatic Diseases: A Nationwide Population-Based Cohort Study - Lo, Chien-Hsien; Wei, James Cheng-Chung; Wang, Yu-Hsun; Tsai, Chin-Feng; Chan, Kuei-Chuan; Li, Li-Ching; Lo, Tse-Hsien; Su, Chun-Hung (Frontiers in Immunology, 2021)
Objectives Hydroxychloroquine (HCQ) is widely used to treat rheumatic diseases including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and Sjögren’s syndrome (SS). Cardiac arrhythmia has been concerned as important safety issue for HCQ. The aim of this study was to investigate whether hydroxychloroquine increases new-onset arrhythmia among patients with RA, SLE or SS. Methods This was a retrospective cohort study that conducted from the longitudinal health insurance database of Taiwan. Patients with newly diagnosed RA, SLE or SS with age ≥20 years old were selected from 2000 to 2012. Patients who received HCQ and without HCQ treatment groups were matched by propensity score to minimize the effect of selection bias and confounders. The Cox proportional hazard model was used to analyse the risk of arrhythmia between the two groups after controlling for related variables. Results A total of 15892 patients were selected to participate and finally 3575 patients were enrolled in each group after matching. There was no different risk of all arrhythmia in patients using HCQ than without HCQ (adjusted hazards ratio 0.81, 95% CI 0.61–1.07) and ventricular arrhythmia as well. The incidence of arrhythmia did not increase when HCQ co-administrated with macrolides. The arrhythmia risk was also not different regardless of daily HCQ dose <400mg or ≥400mg or follow-up duration of ≦4 months or >4 months. Conclusion The administration of HCQ did not increase the risk of all cardiac arrhythmia and ventricular arrhythmia regardless of different duration of treatment (≦4 months or >4 months) or cumulative dose (<400mg or ≥400mg) in patients with common autoimmune diseases such as RA, SLE and SS.